Der TETRISC SoC - Ein resilientes Quad-Core System auf Pulpissimo-Basis - Müller, Wolfgang; Ulbricht, Markus; Li, Lu; Krstic, Milos (5. ITG / GMM / GI -Workshop Testmethoden und Zuverlässigkeit von Schaltungen und Systemen)

A 28-Gb/s 27.2mW NRZ Full-Rate Bang-Bang Clock and Data Recovery in 22 nm FD-SOI CMOS Technology - Iftekhar, Mohammed; Gowda, Harshan; Kneuper, Pascal; Sadiye, Babak; Müller, Wolfgang; Scheytt, Christoph (2023 IEEE BiCMOS and Compound Semiconductor Integrated Circuits and Technology Symposium (BCICTS))

Passio domini? Grundlagen und Entwicklungen chronologischer Systeme im frühen Mittelalter - Englisch, Brigitte (Chroniken als Quellen landesgeschichtlicher Forschung)

Wer kooperiert besser mit wem? – Effekte des Team-Teachings von Lehramtsstudierenden auf die Kompetenzen von Kindern im (inklusiven) naturwissenschaftlichen Sachunterricht. Vortrag auf der Sektionstagung Empirische Bildungsforschung der Arbeitsgruppe für Empirische Pädagogische Forschung (AEPF) und der Kommission Bildungsplanung, Bildungsorganisation und Bildungsrecht (KBBB). Thema: „Schule und Lehrkräfte. Bildung neu denken“. - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva

Effekte eines universitären Trainings zur Lehrerkooperation auf die inklusionsbezogenen Selbstkonzepte von Lehramtsstudierenden. Vortrag auf der Sektionstagung Empirische Bildungsforschung der Arbeitsgruppe für Empirische Pädagogische Forschung (AEPF) und der Kommission Bildungsplanung, Bildungsorganisation und Bildungsrecht (KBBB). Thema: „Schule und Lehrkräfte. Bildung neu denken“. - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

It is a Match: Corporate Entrepreneurship und Effizienzsteigerung - Wach, Bernhard; Krebs, Benjamin; Tomin, Slawa (PERSONALquarterly)

The Dunkl-Laplace transform and Macdonald’s hypergeometric series - Brennecken, Dominik; Rösler, Margit (Transactions of the American Mathematical Society)

Scenario-based Foresight in the Age of Digitalization and Artificial Intelligence – Identification and Analysis of Existing Use Cases - Ködding, Patrick; Ellermann, Kai; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Die Kreuzzüge. Militärisches Mönchtum, Kirchlicher Imperialismus, Gottesfurcht und Menschenverachtung - Janus, Richard

Inklusion und Religionsunterricht. Einführung in eine heterogenitätssensible Religionspädagogik - Janus, Richard

Bibelfeste Terroristen, laichende Aale und eine frustrierte Polizeichefin. Syllas Tzoumerkas Film "Das Wunder im Meer von Sargasso" - Janus, Richard (ta katoptrizomena - Magazin für Kunst, Kultur, Theologie)

Think-aloud beim hochschulischen Mathematiklernen – Ergebnisse einer Pilotierung - Kolbe, Tim (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

Gefürchtet und passiv hingenommen. Aspekte zur Gruppenarbeit in der Lehre - Reis, Oliver (Forschung & Lehre)

Das Grundgesetz als Katalysator zur Konzeptionierung religiöser Bildung in Deutschland. Zum Verhältnis von Bildung und Recht in der Weiterentwicklung des konfessionellen Religionsunterrichts - Reis, Oliver (Recht und Religionen im Weimarer Dreieck. Europäische Anforderungen und Chancen)

AutonomROS: A ReconROS-based Autonomous Driving Unit - Lienen, Christian; Brede, Mathis; Karger, Daniel; Koch, Kevin; Logan, Dalisha; Mazur, Janet; Nowosad, Alexander Philipp; Schnelle, Alexander; Waizy, Mohness; Platzner, Marco (2023 Seventh IEEE International Conference on Robotic Computing (IRC))

On Guaranteeing Schedulability of Periodic Real-time Hardware Tasks under ReconOS64 - Clausing, Lennart; Guetattfi, Zakarya; Kaufmann, Paul; Lienen, Christian; Platzner, Marco (Proceedings of the 19th International Symposium on Applied Reconfigurable Computing (ARC))

Mapping and Optimizing Communication in ROS 2-based Applications on Configurable System-on-Chip Platforms - Lienen, Christian; Nowosad, Alexander Philipp; Platzner, Marco (Proceedings of the 2023 9th International Conference on Robotics and Artificial Intelligence (ICRAI))

fpgaDDS: An Intra-FPGA Data Distribution Service for ROS 2 Robotics Applications - Lienen, Christian; Middeke, Sorel Horst; Platzner, Marco (Proceedings of the 2023 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS))

Towards comparable ratings: Exploring bias in German physician reviews - Kersting, Joschka; Maoro, Falk; Geierhos, Michaela (Data & Knowledge Engineering)
In this study, we evaluate the impact of gender-biased data from German-language physician reviews on the fairness of fine-tuned language models. For two different downstream tasks, we use data reported to be gender biased and aggregate it with annotations. First, we propose a new approach to aspect-based sentiment analysis that allows identifying, extracting, and classifying implicit and explicit aspect phrases and their polarity within a single model. The second task we present is grade prediction, where we predict the overall grade of a review on the basis of the review text. For both tasks, we train numerous transformer models and evaluate their performance. The aggregation of sensitive attributes, such as a physician’s gender and migration background, with individual text reviews allows us to measure the performance of the models with respect to these sensitive groups. These group-wise performance measures act as extrinsic bias measures for our downstream tasks. In addition, we translate several gender-specific templates of the intrinsic bias metrics into the German language and evaluate our fine-tuned models. Based on this set of tasks, fine-tuned models, and intrinsic and extrinsic bias measures, we perform correlation analyses between intrinsic and extrinsic bias measures. In terms of sensitive groups and effect sizes, our bias measure results show different directions. Furthermore, correlations between measures of intrinsic and extrinsic bias can be observed in different directions. This leads us to conclude that gender-biased data does not inherently lead to biased models. Other variables, such as template dependency for intrinsic measures and label distribution in the data, must be taken into account as they strongly influence the metric results. Therefore, we suggest that metrics and templates should be chosen according to the given task and the biases to be assessed.
Keywords: Language model fairness; Aspect phrase classification; Grade prediction; Physician reviews

Characterizing external visualization in mathematics education research: a scoping review - Schoenherr, Johanna; Schukajlow, Stanislaw (ZDM – Mathematics Education)
Abstract External visualization (i.e., physically embodied visualization) is central to the teaching and learning of mathematics. As external visualization is an important part of mathematics at all levels of education, it is diverse, and research on external visualization has become a wide and complex field. The aim of this scoping review is to characterize external visualizations in recent mathematics education research in order to develop a common ground and guide future research. A qualitative content analysis of the full texts of 130 studies published between 2018 and 2022 applied a deductive-inductive coding procedure to assess four dimensions: visualization product or process, type of visualization, media, and purpose. The analysis revealed different types of external visualizations including visualizations with physical resemblance ranging from pictorial to abstract visualizations as well as three types of visualizations with structural resemblance: length, area, and relational visualizations. Future research should include measures of visualization products or processes to help explain the demands and affordances that different types of visualizations present to learners and teachers.
Keywords: General Mathematics; Education